The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/oby.20715
|View full text |Cite
|
Sign up to set email alerts
|

The number of chews and meal duration affect diet‐induced thermogenesis and splanchnic circulation

Abstract: Objective: To determine the effects of the number of chews and meal duration on diet-induced thermogenesis (DIT) and splanchnic blood flow (BF). Methods: Healthy normal-weight subjects (11 subjects in the 100-kcal test and 10 subjects in the 300-kcal test) participated in two trials: a rapid-eating trial and a slow-eating trial. The meal duration and the number of chews were recorded. DIT was calculated from oxygen uptake and body mass, and splanchnic BF was calculated from the diameters of and blood velocitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
43
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 24 publications
(33 reference statements)
5
43
0
Order By: Relevance
“…Longitudinal studies found that fast eating induced weight gain, with the odds ratio of being overweight during a 3-y follow-up being 4.4 times higher in fast eaters than in not-fast eaters (5), and the weight gain during an 8-y follow-up being 1.9 kg in a fast eating group compared to 0.7 kg in moderate and slow eating groups (15). In addition, our recent experimental studies showed that the postprandial energy expenditure was greater for slow eating than fast eating when consuming the same test meal, suggesting that fast eating is related to overweight even in the absence of overeating (25,26). These observations together indicate that fast eating can lead to weight gain via multiple mechanisms.…”
mentioning
confidence: 93%
“…Longitudinal studies found that fast eating induced weight gain, with the odds ratio of being overweight during a 3-y follow-up being 4.4 times higher in fast eaters than in not-fast eaters (5), and the weight gain during an 8-y follow-up being 1.9 kg in a fast eating group compared to 0.7 kg in moderate and slow eating groups (15). In addition, our recent experimental studies showed that the postprandial energy expenditure was greater for slow eating than fast eating when consuming the same test meal, suggesting that fast eating is related to overweight even in the absence of overeating (25,26). These observations together indicate that fast eating can lead to weight gain via multiple mechanisms.…”
mentioning
confidence: 93%
“…Among the above studies, only the study by Kohyama et al (2003) considered the potential effect of body mass index (BMI) and reported that BMI was not significantly different between young and older adults in their study; other studies (Cecilio et al, 2010;Galo et al, 2006Galo et al, , 2007Kohyama et al, 2002;Kohyama & Mioche, 2004;Mioche et al, 2004b;Mishellany-Dutour et al, 2008) had not adjusted for BMI in their analysis. While accumulating data supporting the relationship between chewing behavior and energy hemostasis or body weight status have been published recently (Cassady et al, 2009;Fukuda et al, 2013;Hamada et al, 2014;Li et al, 2011;Smit et al, 2011;Zhu & Hollis, 2014aZhu et al, 2013Zhu et al, , 2014, it raises the possibility that differences in chewing behavior between young and older adults reported in previous studies (Cecilio et al, 2010;Galo et al, 2006Galo et al, , 2007Kohyama & Mioche, 2004;Kohyama et al, 2002;Mioche et al, 2004b;Mishellany-Dutour et al, 2008) may be confounded by body weight status. Therefore, studies that compare chewing behaviors between young and older adults that adjust for these confounding factors are needed; such studies are not only important for a better understanding of aging-related mastication problems, but also may provide additional information to explain for the reduced appetite in older adults, as previous studies reported that increased number of chewing cycles before swallowing results in reduced appetite (Zhu et al, 2013(Zhu et al, , 2014 and reduced food intake (Li et al, 2011;Smit et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Table 2 summarizes the interventions and outcomes of the studies. Nine studies were conducted in the USA [19,20,21,22,23,24,25,26,27], five in Japan [14,28,29,30], four in the UK [17,31,32,33], two in Australia [18,34], two in France [35,36], two in Denmark [15,37], one in Germany [38], one in Spain [39], and one in the Netherlands [16]. The majority of the studies were not blinded, three were double blinded [14,37], and two studies were single blinded [18,24].…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the studies had a sample size <20; only four studies had ≥20 participants [24,33,35,39]. Fifteen studies had only males [14,18,19,21,22,23,25,28,30,33,34,35,36,37,39], eight studies had only females [14,20,24,27,29,31,32,38], and four studies had a mix of males and females [15,16,17,26]. …”
Section: Resultsmentioning
confidence: 99%